2012
DOI: 10.1161/hypertensionaha.111.181123
|View full text |Cite
|
Sign up to set email alerts
|

T Regulatory Lymphocytes Prevent Aldosterone-Induced Vascular Injury

Abstract: Aldosterone mediates actions of the renin-angiotensin-aldosterone system inducing hypertension, oxidative stress, and vascular inflammation. Recently, we showed that angiotensin II-induced hypertension and vascular damage are mediated at least in part by macrophages and T-helper effector lymphocytes. Adoptive transfer of suppressor T-regulatory lymphocytes (Tregs) prevented angiotensin II action. We hypothesized that Treg adoptive transfer would blunt aldosterone-induced hypertension and vascular damage. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
185
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(192 citation statements)
references
References 33 publications
4
185
0
3
Order By: Relevance
“…Several groups have shown that adoptive transfer of Tregs lowers BP and ameliorates cardiac and renal injury in different models of hypertension. [65][66][67][68] Mice deficient in IL-10, an important product of Tregs, develop similar degrees of hypertension in response to angiotensin II, but have severe endothelial dysfunction and vessels from these mice show an increased superoxide production when incubated with angiotensin II. 69 These and other data suggest that Treg-derived IL-10 mediates the beneficial effects of Tregs in hypertension.…”
Section: Tregs and Il-10mentioning
confidence: 99%
“…Several groups have shown that adoptive transfer of Tregs lowers BP and ameliorates cardiac and renal injury in different models of hypertension. [65][66][67][68] Mice deficient in IL-10, an important product of Tregs, develop similar degrees of hypertension in response to angiotensin II, but have severe endothelial dysfunction and vessels from these mice show an increased superoxide production when incubated with angiotensin II. 69 These and other data suggest that Treg-derived IL-10 mediates the beneficial effects of Tregs in hypertension.…”
Section: Tregs and Il-10mentioning
confidence: 99%
“…16 Several experimental studies demonstrated the importance of regulatory T cells in the prevention of immune cell infiltration and the consequent development of hypertension. 44,45 Despite compelling evidence for T-cell involvement as part of the adaptive immune system in the generation and propagation of hypertension, it remains to be determined why T cells infiltrate the kidney, vascular wall and central nervous system. Is it simply a phenomenon secondary to chemokines produced from the reaction of the innate immune system, or is there a specific antigen, not yet identified, involved in the localized adaptive immune response?…”
Section: Adaptive Immune System In the Pathogenesis Of Hypertensionmentioning
confidence: 99%
“…37 T-cell signaling is induced by chemokines and other stimulants and mediated by the activation of Rhoguanine triphosphate hydroxylases, such as Rac1. 38,39 Tregulatory lymphocytes prevent AII-and aldosterone-induced hypertension and vascular injury, 40 and crosstalk occurs between aldosterone and angiotensin signaling. 41 MR activation in macrophages contributes to BP elevation and vascular damages in AII/Nv-nitro-L-arginine methyl ester hypertension and deoxycorticosterone acetate (DOCA) salt hypertension.…”
Section: Rac1-induced Mr Activationmentioning
confidence: 99%